(untitled) (European Journal of Economics, Finance and Business Development, 2024)
This article highlights the impact of industrial production on economic growth. In particular, the impact of industry on economic growth was quantitatively evaluated based on econometric modeling, the share of industrial gross added value in the gross domestic product (GDP) and its dynamics were analyzed. Also, scientific proposals were developed on the basis of the development of industrial sectors to ensure economic growth, increase the efficiency of branch enterprises, expand production and increase their share in exports.